THE IMPORTANCE OF INTENSIVE COURSES IN TEACHING ENGLISH (Лучшие интеллектуальные исследования, 2025)
Abstract: English is perceived today as the main tool of global communication. It plays an important role not only in international relations, but also in the fields of Business, Education, Science and culture. Because of this, the process of learning English has become a necessity for many people. Intensive courses are of particular importance in this process as a method of teaching. Intensive courses allow students to master the language quickly and efficiently in a short time. Such courses often consist of several hours of classes to help students develop language skills intensively.